Peritoneo-venous shunt implantation as a therapy for chylous ascites - Tasnádi, G.; Bihari, I.; Bihari, P. (Phlebologie, 2010)
We report a case of primary chylous ascites in a progressively poor condition with proteinlosing enteropathy, pleural and pericardiac effusion. Therapy: Denver peritoneo- venous shunt was implanted. Three years later the patient became septic and the shunt was removed. Clinical course: Soon after implantation the patient’s condition improved, and in two months he lost 51 kg. After three years fibrinous occlusion of the shunt and sepsis developed. The occlusion could be dissolved with streptokinase. Removing the shunt cured the patient’s septic state. The chylous ascites did not recur. Conclusion: In emergency cases implantation of a peritoneo-venous shunt leads to a rapid relief of the state. Usually this is a palliative treatment, but in this case it gave a final result. Fibrin can deposit on or occlude the drain which can be solved without further complications. If the patient is septic the drain must be removed and the septic state ends.
Keywords: Chylous ascites; peritoneo-venous shunt; septic state; primary lymphatic disease